Between Tradition and Sharia: Resolving Cultural Conflict in Walīmah Infiṣāl through Ibn Qayyim al-Jawziyyah’s Theory of Legal Change - Ismail Keri; Abdulahanaa Abdulahanaa; Ma'adul Yaqien Makkarateng; Hamzah Hamzah; Sylviah Sylviah (De Jure: Jurnal Hukum dan Syari'ah, 2026)
The practice of walīmah infiṣāl (segregated wedding receptions) as a symbol of religious identity in Bone Regency often confronts established traditional marriage cultures, creating potential cultural and religious conflicts in public spaces. This study explores strategies to address these tensions by utilising Ibn Qayyim al-Jawziyyah’s framework for legal change. The research employs a qualitative approach, including normative-juridical analysis and a case study method, in Bone Regency. Data were gathered through participatory observation and in-depth interviews with 20 key informants, including religious scholars (ulama), academics and community leaders, conducted during the field research period. The study identifies three primary conflict resolution strategies used by the community: (1) a preaching strategy to educate on ethical dress and adornment; (2) a tolerance strategy based on recognising diverse schools of thought; and (3) a dialogue strategy to build consensus and practical compromises. Furthermore, three adaptive role models are proposed: (1) a combined model featuring a three-lane seating arrangement (male, female and family) without a physical partition; (2) a modified traditional model incorporating ethical guidance and discouraging monetary donations; and (3) an adapted walīmah infiṣāl model that maintains separation while providing designated spaces for family socialisation. Theoretically, this research demonstrates that Ibn Qayyim al-Jawziyyah’s principles, particularly the al-jam‘u wa al-taufīq (reconciliation) method, provide a constructive framework for harmonising religious mandates in texts with the socio-cultural benefits of local traditions.